Systematic Literature Reviews on Rapid Application Development Information System - Muhammad Anwar Fauzi; Herlandro Tribiakto; Anip Moniva; Fail Amir; Irsyad Khalid Ilyas; Ema Utami (Bulletin of Computer Science and Electrical Engineering, 2023)
Rapid Application Development (RAD) is one of the Software Development Cycle (SDLC) methodologies that are often used by development teams that prioritize time efficiency. The RAD methodology is considered as one of the methodologies that has the shortest completion time compared to other SDLC methodologies. This study aims to validate, update, and expand the previous discussion regarding the universal conditions of RAD model research in the world of software feature development. Objectives can be obtained using a narrative review procedure, which is applied to previously collected literature. This study aims to make conclusions about the model of the RAD methodology which is very effective, supports and constrains the RAD model, and is efficient compared to other development models. Not only that, this research also guides the universal stages in SDLC and the RAD methodology used to integrate these stages.